Structural, electronic, and optical properties of strained si1-xgex alloys - Theodorou, George Os; Tserbak, C.; Kelires, Pantelis C. (My University, 1994)
A systematic study of structural, electronic, and optical properties of strained Si1-xGex alloys, coherently grown on a Si(001) surface, is presented. We find that for bulk alloys the lattice constant deviates from Vegards law, while for the strained alloys it deviates from the results of elasticity theory. The strained alloys are indirect gap materials, with the minimum of the conduction band appearing in the [100] direction. We present results for the indirect as well as the direct gaps. Finally, we investigate the optical properties of strained alloys and present results for the critical energies as a function of the concentration of Ge in them.
Keywords: Alloys; Electronics; Conduction band